2015
DOI: 10.1002/cbin.10464
|View full text |Cite
|
Sign up to set email alerts
|

The role of ghrelin on apoptosis, cell proliferation and oxidant‐antioxidant system in the liver of neonatal diabetic rats

Abstract: Ghrelin is a multifunctional peptide hormone which stimulates appetite and regulates glucose metabolism and adipogenesis. The purpose of this study was to investigate whether ghrelin has protective effects in the liver of streptozocin (STZ) diabetic rats or not. Wistar-type neonatal rats were divided into four groups: I. Controls, II. Ghrelin administrated controls, III. STZ-diabetic rats, and IV. Ghrelin administrated diabetic rats. On the second day after birth, 100 mg/kg STZ was administered intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Gezginci-Oktayoglu et al (43) reported that a combination of selenium and vitamins C and E has a curative effect on hepatic damage. Ghrelin also improves the histopathological changes in the liver (44). Wild ginseng cambial meristematic cells protect the liver against GalN-induced inflammation, and sesamin ameliorates D-GaIN/lipopolysaccharide-induced hepatic damage (45,46).…”
Section: Discussionmentioning
confidence: 92%
“…Gezginci-Oktayoglu et al (43) reported that a combination of selenium and vitamins C and E has a curative effect on hepatic damage. Ghrelin also improves the histopathological changes in the liver (44). Wild ginseng cambial meristematic cells protect the liver against GalN-induced inflammation, and sesamin ameliorates D-GaIN/lipopolysaccharide-induced hepatic damage (45,46).…”
Section: Discussionmentioning
confidence: 92%
“…Ghrelin has several biological actions, including regulating cell survival and proliferation, inhibiting inflammation, and exerting antioxidative effects [ 23 , 24 ]. Previous studies have indicated that the antioxidative effect of ghrelin is based on increasing the activity of endogenous antioxidant enzymes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the functions of ghrelin include improving ingestion, gastric acid secretion and gastrointestinal motility, and protecting the mucous membrane of the digestive system (9). Previous studies have reported that ghrelin exerts anti-inflammatory, antioxidative and neuroprotective effects (10)(11)(12). Therefore, the present study aimed to determine the protective effects of ghrelin against oxidative stress, inducible nitric oxide synthase (iNOS) and inflammation in MIRI mice, and to investigate the mechanisms underlying the cardioprotective effects of ghrelin.…”
Section: Introductionmentioning
confidence: 96%
“…Wang et al (20) demonstrated that ghrelin protects mice against endotoxemia-induced acute kidney injury via the suppression of nitric oxide, and inhibition of TNF-α, IL-1β and IL-6. Koyuturk et al (10) indicated that ghrelin inhibited apoptosis, cell proliferation and the oxidant-antioxidant system via caspase-8 and caspase-3 in the liver of neonatal diabetic rats. Furthermore, Ercan et al (21) suggested that ghrelin treatment suppressed sodium metabisulfite-induced oxidative stress and caspase-3 expression in rat gastric mucosa.…”
mentioning
confidence: 99%